2017
DOI: 10.1504/ijesb.2017.084845
|View full text |Cite
|
Sign up to set email alerts
|

A social affair: identifying motivation of social entrepreneurs

Abstract: Social entrepreneurship is a relatively new object of research and, despite the growing interest it generates in the literature, there is a diversity of definitions and approaches. The objective of this paper is to contribute to the understanding of the motivation of social entrepreneurs by applying the push and pull approach. We study the entrepreneurial motivation of 8 social entrepreneurs. Findings suggest that social entrepreneurs are motivated by a combination of both push and pull factors and drivers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Scholars study differences in personality characteristics between social and commercial entrepreneurs. For example, research found social entrepreneurs to be particularly optimistic (Gabarret, Vedel, and Decaillon 2017), committed (Miller et al 2012), emotional (Miller et al 2012;Ruskin, Seymour, and Webster 2016) and altruistic (Ruskin, Seymour, and Webster 2016). However, the value of the trait approach in understanding social entrepreneurs and difference between entrepreneurs is still debated (Keh, Der Foo, and Lim 2002).…”
Section: Social and Commercial Entrepreneursmentioning
confidence: 99%
“…Scholars study differences in personality characteristics between social and commercial entrepreneurs. For example, research found social entrepreneurs to be particularly optimistic (Gabarret, Vedel, and Decaillon 2017), committed (Miller et al 2012), emotional (Miller et al 2012;Ruskin, Seymour, and Webster 2016) and altruistic (Ruskin, Seymour, and Webster 2016). However, the value of the trait approach in understanding social entrepreneurs and difference between entrepreneurs is still debated (Keh, Der Foo, and Lim 2002).…”
Section: Social and Commercial Entrepreneursmentioning
confidence: 99%
“…Social entrepreneurship is a relatively new subject of research and, despite the growing interest it generates in the literature over more than 20 years, there is a diversity of its definitions and approaches [12], [13]. Social entrepreneurship is seen frequently as a socialized and community phenomenon.…”
Section: A Social Entrepreneurshipmentioning
confidence: 99%
“…Social entrepreneurship is determined by various factors, among them most frequently are: cultural, institutional and economic determinants, access to knowledge and finance beside entrepreneurial capability [19]. Social entrepreneurs are motivated by a combination of both push factors (economic dimension such as to create own job) and pull factors (territorial and social dimensions, it is more about a desire to improve surroundings and to play there social and territorial role in changing everyday life of people in the community and immediate environment) and drivers of motivation are not only at an individual level (personal needs) but also at a social level through the recognition of social needs [12], [20]. Social entrepreneurship is related with passion, tenacity, individual and social innovations, especially in the field of social inclusion [21], [22].…”
Section: A Social Entrepreneurshipmentioning
confidence: 99%
“…Social entrepreneurship is a relatively new subject of research both in developed and developing countries. Despite the growing interest it generates in the literature over more than two decades, there is a plenty and diversity of its definitions (Gabarret et al, 2017;Tien, 2019b;Kee, 2017). Hereafter, for the purpose of further analysis, we present several understandings and perceptions of mainstream researchers on the essence of social entrepreneurship.…”
Section: Overview Of Researches On Social Entrepreneurshipmentioning
confidence: 99%
“…Social entrepreneurs are motivated by a combination of both push factors (economic dimension such as to create own job) and pull factors (territorial and social dimensions, it is more about a desire to improve surroundings and to play there a social and territorial role in changing everyday life of people in the community and immediate environment). The drivers of motivation of social entrepreneurs are not only at the individual level (realizing personal needs) but also at the social level (through recognition and corecognition of social needs) (Gabarret et al, 2017;Notais & Tixier, 2017).…”
Section: Overview Of Researches On Social Entrepreneurshipmentioning
confidence: 99%